Recent applications of macrocycles in supramolecular catalysis - Wang, Conghui (2023)
Numerous supramolecular macrocycles have been utilized for developing catalysts by exploiting their specific molecular recognition and ability to form inclusion complexes through noncovalent interactions. The cyclic structure and modified functional groups of these macrocycles can influence substrate and transition state stability, as well as reaction selectivity. The inner cavities of these macrocycles are particularly beneficial, as they enable substrates to adopt preorganized arrangements and serve as versatile platforms for highly efficient supramolecular catalytic systems. This minireview provides an overview of recent advancements in supramolecular catalysis using various macrocycles, such as crown ethers, cyclodextrins, calixarenes, pillararenes, cucurbiturils, and other novel macrocycles.